Efficacy and safety of PD‐1 inhibitor combined with antiangiogenic therapy for unresectable hepatocellular carcinoma: A multicenter retrospective study. (10th April 2022) - Yao, Junlin; Zhu, Xudong; Wu, Zhiheng; Wei, Qing; Cai, Yibo; Zheng, Yu; Hu, Xinyu; Hu, Hong; Zhang, Xiangyu; Pan, Hongming; Zhong, Xian; Han, Weidong
Abstract: Background: Immunotherapy‐antiangiogenesis combination therapy has achieved excellent survival outcomes in hepatocellular carcinoma (HCC) in clinical trials. However, the combination therapy for HCC outside clinical trials is not well studied, and predictive factors are lacking. Here, we retrospectively analyzed the efficacy and safety of immunotherapy‐antiangiogenesis combination therapy in unresectable HCC patients in a real‐world setting. Methods: We conducted a four‐center, retrospective study of unresectable HCC patients who received the combination of programmed death 1 ( PD‐1) inhibitor and antiangiogenic agent between April 2018 and July 2021 in China. Results: In total, 136 patients were enrolled in the cohort. The objective response rate (ORR) and disease control rate (DCR) were 38.0% and 81.8%, respectively. The median time to progression (TTP), progression‐free survival (PFS), and overall survival (OS) were 7.2, 7.3, and 19.6 months, respectively. The multivariate analysis indicated that ECOG performance status score (PS) 2 was a significantly independent negative factor of ORR. Moreover, ECOG PS 2, peritoneum metastasis and previous immunotherapy were found to be independent negative predictors of PFS. A shorter OS was associated with ECOG PS 2, peritoneum metastasis, the presence of previous immunotherapy, Child‐Pugh stage B, and high alpha‐fetoprotein (AFP) concentration. One hundred and twenty‐five patients (91.9%) reported adverse events (AEs) with any grade. Conclusion: We elucidated the efficacy and safety of immunotherapy‐antiangiogenesis combination therapy and identified potential predictors for response and survival in a real‐world cohort of patients with unresectable HCC. Abstract : Immunotherapy‐antiangiogenesis is an efficacious strategy for unresectable HCC. We identified potential predictors for response and prognosis in HCC.